2002
DOI: 10.1021/bi0201318
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Four-Copper Laccase Complexed with an Arylamine:  Insights into Substrate Recognition and Correlation with Kinetics,

Abstract: Laccases are multicopper oxidases that catalyze the oxidation of a wide range of phenols or arylamines, and their use in industrial oxidative processes is increasing. We purified from the white rot fungus Trametes versicolor a laccase that exists as five different isozymes, depending on glycosylation. The 2.4 A resolution structure of the most abundant isozyme of the glycosylated enzyme was solved. The four copper atoms are present, and it is the first crystal structure of a laccase in its active form. The cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
361
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 494 publications
(378 citation statements)
references
References 33 publications
12
361
2
3
Order By: Relevance
“…CueO can oxidize a range of substrates in vitro, including catechols, siderophores, and Fe(II) (10), and this activity is greatly enhanced in the presence of excess (ϳ100 M) copper(II) ions (10,15), suggesting that binding of a labile copper is important for enzymatic activity. We recently determined the crystal structure of CueO at 1.4-Å resolution (15) and showed that its structure is similar to that of other multicopper oxidases, such as ascorbate oxidase (16) and several laccases (17)(18)(19). As expected, CueO contains a T1 "blue copper" site, near the point at which the larger substrate is believed to bind, as well as a trinuclear copper center, where oxygen reduction occurs.…”
mentioning
confidence: 68%
“…CueO can oxidize a range of substrates in vitro, including catechols, siderophores, and Fe(II) (10), and this activity is greatly enhanced in the presence of excess (ϳ100 M) copper(II) ions (10,15), suggesting that binding of a labile copper is important for enzymatic activity. We recently determined the crystal structure of CueO at 1.4-Å resolution (15) and showed that its structure is similar to that of other multicopper oxidases, such as ascorbate oxidase (16) and several laccases (17)(18)(19). As expected, CueO contains a T1 "blue copper" site, near the point at which the larger substrate is believed to bind, as well as a trinuclear copper center, where oxygen reduction occurs.…”
mentioning
confidence: 68%
“…One methoxy group of SA forms a hydrogen bond with the surface-exposed histidine His419, one of the Cu1 ligands, by N-O hydrogen bond. ABTS is reported bonding to His497, the other Cu1 ligand, which is another binding mode also observed in other fungal laccases/substrates complexes (Bertrand et al, 2002;Kallio et al, 2009;Matera et al, 2008). In CotA laccase, Cu1 is coordinated by two histidines including His419 and His497, both surface-exposed and available for substrate binding.…”
Section: Sa Binding To Cota Laccasementioning
confidence: 55%
“…To date, four crystal structures of laccase/ligand complex have been reported: laccase from Trametes versicolor (TvL)/2,3-xylidine complex (Bertrand et al, 2002), laccase from Trametes trogii (TtL)/p-toluate complex (Matera et al, 2008), laccase from Melanocarpus albomyces (MaL)/2,6-dimethoxyphenol (DMP) complex (Kallio et al, 2009) and CotA/ABTS complex from Bacillus subtilis (Enguita et al, 2004). Among these ligands, DMP (a phenolic compound) and ABTS (a non-phenolic compound) are efficient synthetic mediators for laccases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MnP and LiP structures are very similar in that they are heme-containing glycoproteins which require hydrogen peroxide as an oxidant (POULOS et al, 1993;. Laccase, a copper-containing oxidase, utilizes molecular oxygen as oxidant to oxidize phenolic rings to phenoxyl radicals (BERTRAND et al, 2002).…”
Section: Wallberg 2014) Hexose Fermentation Is a Well-known Processmentioning
confidence: 99%